A Study of the Effectiveness of E-Commerce Adoption among Small and Medium-sized Enterprise (SME) in Postnatal Care Services Industry: a Case Study in Selangor, Malaysia - I. , Masbuqin; SM. , Sharif; A. , Isa; A.Y.M. , Noor; A.Z. , Samsudin (International Journal of Psychosocial Rehabilitation, 2020)
The paper aims to provide an insight about factors affecting business-to-business e-commerce (EC) adoption and implementation in small to medium-sized enterprises (SMEs), highlighting among postnatal care services industry. However, EC adoption by SME in developing countries has faced many challenges that we have not adequately ad-dressed due to the complex nature of EC adoption in such countries. We based the re-search on an extensive literature review, focused on proposing a theoretical model of technological, environmental and organizational factors (TOE) influencing e-commerce adoption and implementation. Thus, the first and second research goals focused on this re-search is to identify the characteristics and perception of SMEs’ managers among Postnatal Care Service industry towards E-Commerce (EC) adoption and explaining the factors from the technological, organizational and environmental context affecting SMEs in post-natal care services industry adopting e-commerce. Finally, the research also covers critical studies, as it tries to provide the key strategies that we suggested to the organizations in creating awareness towards E-Commerce platform among SMEs in postnatal care services which help to get an overview and understanding in adopting e-commerce platform in that industry. The results of the empirical research provide an indication to SME among post-natal care services industry interested in adopting and conducting business-to-business e-commerce. This paper both contributes to enhancing the understanding of the factors affecting business-to-business EC adoption and implementation in SME and provides some interesting perspectives from the postnatal care services industry.